2014
DOI: 10.4028/www.scientific.net/amr.919-921.1262
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-Induced Dynamic Response of Submerged Floating Tunnel Tether Based on Wake Oscillator Model

Abstract: To study the vibration response of submerged floating tunnel tether under the combined action of vortex-induced vibration and parametric vibration, a non-linear vibration equation based on wake oscillator model is set up taking the geometric nonlinearity of tether into account, in which effect of tube on tether is simplified as axial excitation. An approximate numerical solution of planning submerged floating tunnel tether is obtained by applying Galerkin method and Runge-kutta method. The variation degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For the vibration analysis of SFT, Ge et al [17] and Kang et al [18] applied the von der Pol equation to simulate the VIV of the SFT in flow, and studied the influence of the spacing of the anchor chain on the vibration amplitude of the tunnel. Su and Sun [19] utilised the wake oscillation model to simulate the VIV of the SFT. It was found that the vortex-induced vibration resonance occurred and the axial stress of the structure increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…For the vibration analysis of SFT, Ge et al [17] and Kang et al [18] applied the von der Pol equation to simulate the VIV of the SFT in flow, and studied the influence of the spacing of the anchor chain on the vibration amplitude of the tunnel. Su and Sun [19] utilised the wake oscillation model to simulate the VIV of the SFT. It was found that the vortex-induced vibration resonance occurred and the axial stress of the structure increased significantly.…”
Section: Introductionmentioning
confidence: 99%